Inflammation of left atrial epicardial adipose tissue is associated with paroxysmal atrial fibrillation - Kusayama, Takashi; Furusho, Hiroshi; Kashiwagi, Haruka; Kato, Takeshi; Murai, Hisayoshi; Usui, Soichiro; Kaneko, Shuichi; Takamura, Masayuki (Journal of cardiology, 2016)
Although an increased epicardial adipose tissue (EAT) volume around the left atrium (LA) is related to the atrial fibrillation (AF) burden, the role of EAT inflammation in AF is unclear. We investigated the association between AF and inflammation of the EAT around the LA. We retrospectively identified regions of EAT around the LA and measured the density of these areas using computed tomography (CT). A total of 32 patients who underwent their first catheter ablation for paroxysmal AF (PAF) were enrolled (mean age 62.5±11.1 years). Patients without a history of AF (n=32), but who underwent cardiac CT and were matched by age, sex, and metabolic risk factors, were enrolled in the control group (62.2±12.1 years). The mean EAT density around the LA was significantly higher in the PAF group than in the control group (−108.1±6.7 vs. −111.6±5.5 Hounsfield units; p=0.02), while the densities of subcutaneous adipose tissue (SAT) in the abdomen and thorax did not differ between the two groups. In a multiple logistic regression analysis, a higher EAT density was significantly associated with the presence of PAF after adjusting for other risk factors (odds ratio: 1.25; 95% confidence interval: 1.08–1.45, p=0.003). This study supports the hypothesis that inflammation of EAT around the LA, but not SAT, is related to the presence of PAF.